2021
DOI: 10.3390/bioengineering8050069
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Multipotent Mesenchymal Stromal Cells as Autologous Therapy for Osteonecrosis: Effects of Age and Underlying Causes

Abstract: Bone marrow (BM) is a reliable source of multipotent mesenchymal stromal cells (MSCs), which have been successfully used for treating osteonecrosis. Considering the functional advantages of BM-MSCs as bone and cartilage reparatory cells and supporting angiogenesis, several donor-related factors are also essential to consider when autologous BM-MSCs are used for such regenerative therapies. Aging is one of several factors contributing to the donor-related variability and found to be associated with a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 223 publications
0
7
0
Order By: Relevance
“…Furthermore, special attention should be paid to the efficiency of MSCs and PRP formulation injection. It had been proved that the combinatorial therapy of MSC core decompression played a positive role in treating ONFH [ 43 ]. In this present study, PRCR and UC-MSCs were delivered to the hip joints via ultrasound-guided intra-articular injections, which possesses many advantages, such as real-time visualization, safety, and portability [ 30 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, special attention should be paid to the efficiency of MSCs and PRP formulation injection. It had been proved that the combinatorial therapy of MSC core decompression played a positive role in treating ONFH [ 43 ]. In this present study, PRCR and UC-MSCs were delivered to the hip joints via ultrasound-guided intra-articular injections, which possesses many advantages, such as real-time visualization, safety, and portability [ 30 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study is uniquely focused on the cross-talk between cartilage and SB in OA and investigated EV production from a specific type of SB cells, SB MSCs, which are directly implicated in SB OA pathology and cartilage destruction “from below” [ 60 62 ]. Although SB MSCs from healthy amputees would be a better control than the MSCs from bone marrow used in this work, these samples are difficult to access while MSCs from amputated knees from diabetics could carry underlying negative effects such as described previously [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells can differentiate into a variety of cell lines (such as bone cells, osteoblasts, and endothelial cells) (Fan et al, 2015;Hernigou et al, 2015;Sui et al, 2019). Bone marrow mesenchymal stem cells are accessible to culture and expand in vitro and accelerate bone regeneration by differentiating into osteoblasts (Le et al, 2020;Song et al, 2020;Zhu et al, 2020;El-Jawhari et al, 2021). Previous studies have shown that bone marrow mesenchymal stem cells secrete a variety of growth factors, cytokines, and other biologically active molecules to regulate the damage and repair process of ischemic tissue after transplantation (Herrmann et al, 2011).…”
Section: Combination Of Polymers and Bioactive Factors With Osteogenesis Functionmentioning
confidence: 99%